The gimmicks : a novel - McCormick, Chris, 1987- (Harper, an imprint of HarperCollinsPublishers, 2020)
This exuberant, wholly original novel begins in Kirovakan, Armenia, in 1971. Ruben Petrosian is a serious, solitary young man who cares about two things: mastering the game of backgammon to beat his archrival, Mina, and studying the history of his ancestors. Ruben grieves the victims of the 1915 Armenian Genocide, a crime still denied by the descendants of its perpetrators, and dreams of vengeance. When his orphaned cousin, Avo, comes to live with his family, Ruben<U+2019>s life is transformed. Gregarious and physically enormous, with a distinct unibrow that becomes his signature, Avo is instantly beloved. He is everything Ruben is not, yet the two form a bond they swear never to break. But their paths diverge when Ruben vanishes<U+2014>drafted into an extremist group that will stop at nothing to make Turkey acknowledge the genocide. Unmoored by Ruben<U+2019>s disappearance, Avo and Mina grow close in his absence. But fate brings the cousins together once more, when Ruben secretly contacts Avo, convincing him to leave Mina and join the extremists<U+2014>a choice that will dramatically alter the course of their lives. Left to unravel the threads of this story is Terry “Angel Hair” Krill, a veteran of both the US Navy and the funhouse world of professional wrestling, whose life intersects with Avo, Ruben, and Mina<U+2019>s in surprising and devastating ways.